Effect of six weeks` isometric strength training compared to traditional strength training on gains in strength, power, and speed in male academy soccer players - Bailey, L. S.; Phillips, J.; Farrell, G.; McQuilliam, S. J.; Erskine, R. M. (Research Quarterly for Exercise and Sport, 2025)
Purpose: Elevated sport-specific physical demands and congested fixture schedules leave little recovery time and augment fatigue levels in soccer players. Compared to traditional strength training (TST), isometric strength training (IST) may elicit comparative improvements in strength and performance-related parameters in soccer players, while reducing fatigue during periods of elevated competitive loading.